A water-soluble fluorescence chemosensor for the sequential detection of Zn2+ and pyrophosphate in living cells and zebrafish - Kang, Ji Hye; Han, Jiyeon; Lee, Hyojin; Lim, Mi Hee; Kim, Ki-Tae; Kim, Cheal (Dyes and pigments, 2018)
A new simple aminohydantoin-based fluorescent chemosensor 1 was designed for sequential detection of Zn2+ and pyrophosphate in a near-perfect aqueous solution. 1 exhibited significant fluorescence intensity in the presence of Zn2+, and the resulting 1-Zn2+ complex showed subsequently the fluorescent quenching with pyrophosphate. The detection limit (0.32 μM) of 1 for Zn2+ was far lower than the guideline of World Health Organization in drinking water. 1 was used to determine Zn2+ concentration in various water samples. In addition, chemosensor 1 could be applied to sequentially detect Zn2+ and pyrophosphate in living cells and zebrafish. The sensing mechanism of Zn2+ by 1 was proposed to be an intramolecular charge transfer with theoretical calculations. [Display omitted] •A water-soluble fluorescent chemosensor 1 was designed for sequential detection of Zn2+ and pyrophosphate (PPi).•Detection limit (0.32 μM) of 1 for Zn2+ was much lower than the WHO guideline (76 μM) for Zn2+ in drinking water.•Sensor 1 could be applied to sequentially detect both Zn2+ and PPi in living cells and zebrafish.•Sensing mechanism of 1 toward Zn2+ was explained by theoretical calculations.